The Importance of Fulfilling Nutrition for Pregnant Women and Toddlers in Preventing Stunting to Improve the Quality of Human Resources in Batu Cepet Subdistrict, Tangerang - Megaster, Tekni (Jurnal Pengabdian Masyarakat Bestari, 2024)
Stunting is a serious nutritional problem that occurs when a child's physical development is permanently hampered, due to chronic malnutrition in the early stages of growth. Stunting prevention requires a comprehensive approach involving government, society and the health sector. The main risk factors associated with stunting include poor nutrition during pregnancy, low nutrition during the first 1,000 days of life (from conception to two years of age), poor hygiene, and infectious diseases. Interventions to prevent stunting include providing nutritional education for pregnant women, encourage exclusive breastfeeding, provide nutritional supplements to children, and improve children's health, access to sanitation and drinking water. These programs must be implemented within a framework that allows fair and sustainable access for all community groups, including those at high risk.